Understanding Confucianism in West Kalimantan - Samsul Hidayat; Reviewed by: Farninda Aditya (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
What is Confucianism? What are its teachings? What is its culture? How did it grow in Indonesia? What is Confucianism like in West Kalimantan? The book, Agama Konghucu (Confucianism) written by Samsul Hidayat, was written to answer those questions. The author of this book, a lecturer at the State Institute of Islamic Studies (IAIN) of Pontianak, has long been doing a study on Confucianism in his capacity as an expert in the field of comparative religion.